2022
DOI: 10.1097/j.pain.0000000000002784
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind phase II randomized controlled trial of an online cognitive bias modification for interpretation program with and without psychoeducation for people with chronic pain

Abstract: Supplemental Digital Content is Available in the Text.Cognitive bias modification of interpretation improved pain severity and pain interference compared with placebo. Psychoeducation did not improve the efficacy of cognitive bias modification of interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Cognitive Bias Modification for Interpretation is also low impact for recipients, with each training session taking as little as 15 minutes. 29 Although other psychological factors are likely to be relevant to pain impact in endometriosis, and should be investigated, the current results demonstrate the unique relationship between interpretation bias and pain-related impact. As such, CBM-I has potential to be included in interventions for endometriosis-related pain impact and it is clearly an empirical question as to whether CBM-I would be efficacious for people with endometriosis.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Cognitive Bias Modification for Interpretation is also low impact for recipients, with each training session taking as little as 15 minutes. 29 Although other psychological factors are likely to be relevant to pain impact in endometriosis, and should be investigated, the current results demonstrate the unique relationship between interpretation bias and pain-related impact. As such, CBM-I has potential to be included in interventions for endometriosis-related pain impact and it is clearly an empirical question as to whether CBM-I would be efficacious for people with endometriosis.…”
Section: Discussionmentioning
confidence: 60%
“…There is a voluminous literature that confirms that threat-related interpretations can be modified and when modified through a procedure known as Cognitive Bias Modification for Interpretation (CBM-I) reduce anxiety. 16,19 Preliminary evidence for CBM-I in pain shows that these interventions are effective in reducing interpretation bias and pain outcomes such as pain severity, pain interference and pain-related fear, 29 and negative emotion and attentional bias in chronic pain. 1 In the current landscape where endometriosis is predominantly medically managed, with limited efficacy and considerable cost, 4 there is a clear and urgent need for accessible and evidence-based psychological interventions, such as CBM-I.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are also consistent with recent research that has found that interventions to reduce interpretation bias can lead to large reductions in fear of cancer progression (Pradhan et al, submitted) and moderate reductions in pain outcomes. 32 As such, interpretation bias and fear of progression may be useful targets for future interventions to reduce the impact of pain in endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…27 This large study found that interpretation bias was associated with pain interference in people with endometriosis and also that those with endometriosis pain showed greater interpretation bias than an endometriosis-free Pearson correlations between endometriosis-specific imagery, fear of progression, and pain outcomes. 32 As such, interpretation bias and fear of progression may be useful targets for future interventions to reduce the impact of pain in endometriosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation